Analisis Yuridis terhadap Kasus Gugatan Perbuatan Melawan Hukum atas Ketidakabsahan Peralihan Hak Milik Benda Bergerak (Studi Kasus Putusan Mahkamah Agung Nomor 1081/K/PDT/2018) - Fathalya Laksana (Kosmik Hukum, 2020)
The legal requirements are regulated in Article 1320 of the Civil Code (KUHPerdata). If the valid conditions of the promise are not fulfilled, then the law that results is that the agreement can be canceled or null and void. In the Court's practice contained in the Supreme Decision Number 1081K / PDT / 2018, there was a sale and purchase agreement between the Plaintiff's husband and the Defendant, the sale and purchase agreement was made by the Plaintiff's partner without the consent of the Plaintiff as his legal wife. Supreme Court Decision No. 1081K / PDT / 2018 stated that the sale and purchase agreement was invalid and null and void. Apart from that, in its decision, the Defendant's UN Supreme Court had committed an illegal act. The research method used is a normative juridical approach using secondary data obtained from literature studies, namely statutory regulations, legal theories, and the opinions of leading legal scholars. This research uses descriptive analytical research specifications that describe the regulations that are in accordance with legal theories that oversee the implementation practices of the problems under study. The data analysis method used is qualitative normative method. Based on the research results, it can be denied that the sale and purchase agreement in the Supreme Court Decision Number 1081K / PDT / 2018 is not legally valid. The agreement does not fulfill the validity requirements of the agreement in Article 1320 of the Civil Code, namely halal skills and causes because it violates Article 36 paragraph (2) of the Marriage Law No. 1 of 1974 resulting in the sale and purchase agreement to be null and void.Keywords: Buying and Selling, Acts against the Law, Agreement, Marriage, Collective Property